Development of Learning Tools Using Discovery Learning Model Equipped with Science Marble Games to Improve Student's Critical Thinking Skills (Unnes Science Education Journal, 2022)
This study aims to determine the characteristics and feasibility of the discovery learning model assisted by marble science games which was developed to improve students' critical thinking skills. This type of research is a research and development study with the ADDIE research model. The research subjects were students of class VIII SMP Kesatrian 1 Semarang. The research data were obtained from the feasibility test of the device developed by the experts as well as a questionnaire about the use of marble games as media science. The results of the due diligence analysis by the experts were stated to be very suitable for use with an average percentage of 83.88%. Questionnaire students' responses regarding the use of marble games science media were stated to be suitable for use with a percentage of 79.67%. Based on this it can be concluded that the development of discovery learning models assisted by science marble games is very feasible to be used to improve students' critical thinking skills.